Phenylbutyrate Up-regulates the DJ-1 Protein and Protects Neurons in Cell Culture and in Animal Models of Parkinson Disease - Zhou, Wenbo (American Society for Biochemistry and Molecular Biology, 2011)
Parkinson disease is caused by the death of midbrain dopamine neurons from oxidative stress, abnormal protein aggregation, and genetic predisposition. In 2003, Bonifati et al. (23) found that a single amino acid mutation in the DJ-1 protein was associated with early-onset, autosomal recessive Parkinson disease (PARK7). The mutation L166P prevents dimerization that is essential for the antioxidant and gene regulatory activity of the DJ-1 protein. Because low levels of DJ-1 cause Parkinson, we reasoned that overexpression might stop the disease. We found that overexpression of DJ-1 improved tolerance to oxidative stress by selectively up-regulating the rate-limiting step in glutathione synthesis. When we imposed a different metabolic insult, A53T mutant α-synuclein, we found that DJ-1 turned on production of the chaperone protein Hsp-70 without affecting glutathione synthesis. After screening a number of small molecules, we have found that the histone deacetylase inhibitor phenylbutyrate increases DJ-1 expression by 300% in the N27 dopamine cell line and rescues cells from oxidative stress and mutant α-synuclein toxicity. In mice, phenylbutyrate treatment leads to a 260% increase in brain DJ-1 levels and protects dopamine neurons against 1-methyl 4-phenyl 1,2,3,6-tetrahydropyridine (MPTP) toxicity. In a transgenic mouse model of diffuse Lewy body disease, long-term administration of phenylbutyrate reduces α-synuclein aggregation in brain and prevents age-related deterioration in motor and cognitive function. We conclude that drugs that up-regulate DJ-1 gene expression may slow the progression of Parkinson disease by moderating oxidative stress and protein aggregation.